PENERAPAN METHODOLOGY SIX SIGMA UNTUK MENGURANGI PEMBOROSAN BIAYA OPERASIONAL WASTE WATER TREATMENT DI PT CLARIANT INDONESIA (STUDI KASUS DI PERUSAHAAN KIMIA) - Nur Fadilah Fatma; Segi Anggi Pradipta (Journal Industrial Manufacturing, 2018)
One of the method used to improve of process to give the solution to increase process standart in internal manufacturing purpose to minimize defect or non conforming and reduce waste so the trend of failure product reduced in period is six sigma method. Through of application cycles of DMAIC (Define, Measure, Analyze, Improve and Control) in six sigm, so one of problem can to clear define the root causes and can to improve with structural. This riset in PT Clariant Indonesia Tangerang Site, in Waste Water Treatment analysis costing needed to operasional water treatment in one year. Where there are several cost aloction not yet effective and efficient so occur waste of operational costing Waste Water Treatment in 2015. Result of the riset is success to defined several root causes and defined several solution to tackle problem waste of cost operational in Waste Water Treatment. In the end of riset success to reduce operational cost Waste Water Treatment till 360 mio IDR in 6 months Control phase. Keyword : Quality Control, Six Sigma, DMAIC, Waste Water Treatment, Continuous Improvement.